ECONOMIC JOURNAL OF EMERGING MARKETS : Infrastructure and inequality: An empirical evidence from Indonesia - Amien Makmuri (Fak. Ekonomi UII, 2017)
This research is an attempt to study the empirical relationship between infrastructure and income inequality in Indonesia. It uses panel data covering 32 provinces. The model is estimated by simple pooled OLS, fixed-effect and random-effect models. We find that road and telecommunication quantities tend to boost income inequality, while electricity quantity, airport quantity, and airport quality have a favorable impact on the distribution of income and help to alleviate income inequality. Whereas, when these different categories of infrastructure are formed as synthetic indices, the relation between these indices and income inequality lends support to the idea that infrastructure increases income inequality.